Ploidy of Bacillus subtilis, Bacillus megaterium, and three new isolates of Bacillus and Paenibacillus - Böttinger, Benjamin; Zerulla, Karolin; Soppa, Jörg (PeerJ PrePrints, 2014)
Bacteria were long assumed to be monoploid, maintaining one copy of a circular chromosome. In recent years it became obvious that the majority of species in several phylogenetic groups of prokaryotes are oligoploid or polyploid, e.g. in halophilic and methanogenic archaea, proteobacteria, and cyanobacteria. The present study aimed at investigating the distribution of ploidy in an additional group of prokaryotes, i.e. in the gram-positive genus Bacillus. First, the numbers of origins and termini of the two laboratory strains Bacillus subtilis and Bacillus megaterium were quantified using an optimized real time PCR approach. B. subtilis was found to be mero-oligoploid in exponential phase with, on average, 5.9 origins and 1.2 termini. In stationary phase the average numbers of origins per cell was considerably smaller. B. megaterium was found to be polyploid in exponential phase with about 12 copies of the origin and terminus. Again, the ploidy level was down-regulated in stationary phase. To verify that oligo-/polyploidy is not confined to strains with a long history of growth in the laboratory, three strains were newly isolated from soil, which were found to belong to the genera of Bacillus and Paenibacillus. All three strains were found to be oligoploid with a growth-phase dependent down-regulation of the ploidy level in stationary phase. Taken together, these results indicate that oligo-/polyploidy might be more widespread in Bacillus and related genera than assumed until now and that monoploidy is not typical.
Keywords: Bacillus; Bacillus subtilis; Bacillus megaterium; polyploidy; oligoploidy; genome copy number; DNA content; mero-oligoploidy; origin of replication